The Influence of the Environment on Officer-Involved Shootings - Keller, Tyler (Homicide studies, 2023)
Research on officer-involved shootings has covered many methods and designs, with a majority focusing on macro-level approaches to understanding the shooting event. Research designs which incorporate place are limited, but what does exist demonstrates the relevance of the micro-environment to contextualize the many factors which give rise to the shooting event. This research further explores the importance of the micro-environment by examining how crime generators and attractors, conceptualized as the built environment, can be utilized to understand where police officers are more likely to discharge their weapon. Data on police shootings in Philadelphia, PA which occurred between 2015 and 2019, along with data describing the environmental landscape of the city are used in conjunction with variables previously determined to be related to shooting events. This analysis uses a three-pronged approach to understanding the relevance of the micro-environment in officer-involved shootings. Results indicate that the most important predictor of police shootings are levels of violent crime. Violent crime rates, in turn, are significantly related to the built environment. The built environment, then, has an indirect relationship to the places where police are most likely to discharge their weapon which is mediated through the violent crime rate.